A case of primary pulmonary leiomyosarcoma completely resected after neoadjuvant chemotherapy - Kazuhisa Tanaka; Takekazu Iwata; Kai Nishii; Yukiko Matsui; Tsukasa Yonemoto; Hidetada Kawana; Makiko Itami; Shigetoshi Yoshida; Toshihiko Iizasa (Surgical Case Reports)
Abstract Background Primary pulmonary leiomyosarcoma is a rare malignant tumor. We herein report a case of primary pulmonary leiomyosarcoma that was completely resected by surgery after neoadjuvant chemotherapy. Case presentation A 60-year-old man presented with cough. Chest computed tomography showed an 11-cm mass in the right upper lobe of the lung that had invaded the superior vena cava. Endobronchial ultrasound-guided transbronchial needle aspiration revealed leiomyosarcoma of the lung. We considered complete resection of the tumor to be very difficult because of the tumor invasion into the right atrium inflow of the superior vena cava, so we performed chemotherapy using doxorubicin for five cycles. After chemotherapy, the tumor size decreased to 5.6 cm, and we performed right upper lobectomy with combined resection of the superior vena cava. The tumor was completely resected by surgery. The patient is alive without recurrence 17 months postoperatively. Conclusions We encountered a case of primary pulmonary leiomyosarcoma that was successfully treated by surgery after neoadjuvant chemotherapy. Doxorubicin monotherapy was effective in this case. Surgery combined with neoadjuvant chemotherapy should be considered for such cases, as a long-term survival can be achieved by complete resection of primary pulmonary leiomyosarcoma.